The Role of Arts in Promoting Tourism: A Case of tourism Development in Thamel Area - Bhatta, Chiranjivi (Journal of Advanced Academic Research, 2017)
Thamel is a touristic area in Kathmandu which has become the main attraction for tourists for the last more than three decades. It is popularly known as the heart of tourists industry in Kathmandu. It was developed along with the arrival of hippies, many of them were artists too. Before that, the tourist attraction was concentrated in Jhonchen area. Hippies came to Nepal in search of enlightenment and spent weeks in Thamel. Along with the tourism promotion through arts and culture, there are lots of challenges in promoting arts and tourism in Thamel which needs special attention from the government of Nepal. It is crucial to recognize the important role that arts play in the positive and healthy tourism development of any society. Government needs to have strategies for partnership between arts, tourism and economic development because it is the key to foster a strong tourism destination. The union of arts and tourism celebrates human authenticity, and increases opportunities for self improvement and creates more genuine experiences along with the employment opportunities directly and indirectly.